Autogenous Electron Acceleration by Ion Flow Vortex in Space Plasmas - C. M. Liu; J. B. Cao; Y. Y. Liu; E. A. Kronberg; X. N. Xing; B. N. Zhao; P. W. Daly (The Astrophysical Journal)
Plasma flow vortexes are ubiquitous in space and astrophysical settings and play a vital role in energy and mass transport, contributing to formation of stars and planets, launching and dissipation of astrophysical jets, and coupling between planetary magnetospheres and ionospheres. Here we present in situ observations showing that energetic electrons with energies up to 250 keV can be directly generated inside an ion flow vortex with finite spatial scale. The electron acceleration is achieved by establishment of Fermi acceleration trap and parallel electrostatic potential within the flow vortex, leading to dramatic enhancement of energetic electron flux by at least 1 order of magnitude. The accelerated electrons can drive mass and energy transport along local magnetic field lines and serve as a free energy source for broadband electrostatic emissions. Our observations, suggesting that the ion flow vortex can serve as novel electron accelerators, can be fundamentally important for understanding energetic phenomena in the cosmos, such as nonthermal emissions near astrophysical jets and killer electrons in geospace.